Suppressed Ion Chromatographic Analysis of Anionic Macroelements in Nutmeg (Myristica fragrans) Diversity Specific to North Maluku - Muhammad Amin; Deasy Liestianty; Abu Rahmat Ibrahim; Nahdiah Amin; Budhi Oktavia (ALCHEMY Jurnal Penelitian Kimia, 2024)
This study proposed an ion chromatography method for analyzing anionic macroelements (fluoride, chloride, nitrite, bromide, nitrate, sulfate, and phosphate), and applied it to nutmeg (Myristica fragrans) diversity to explore the potential of nutmeg as an electrolyte. The analysis method was based on a suppressed conductivity system that simultaneously analyzed the anionic macroelements on Metrohm Supp A 250/4.0 column using 8.0 mM sodium carbonate (Na2CO3) and 0.25 mM sodium bicarbonate (NaHCO3) as a mixture eluent. Excellent peak resolution and completed separation were achieved within 18 min when the flow rate of the detector was 0.8 mL/min. The peak height with calibration curves at 2.5 ‒ 30.0 mg/L concentration ranges was obtained for all anionic macroelements. All collected nutmeg samples were specific to North Maluku. Based on the standard samples used, the analysis results revealed that only four anionic macroelements (chloride, nitrate, sulfate, and phosphate) were found in the nutmeg samples, and the concentration of each anion (e.g., chloride ion, and so) was different for each type of nutmeg. The highest total of anionic macroelements concentration was found in the Myristica succedanea (1605.05 mg/kg) nutmeg sample, while Myristica specioga had the lowest (661.76 mg/kg). The method was validated regarding the detection limit (LOD) and reproducibility.